Guest

prove that (sec^3θ/sec^2θ-1)+(cosec^3θ/cosec^2θ-1)=secθcosecθ(secθ+cosecθ)

prove that (sec^3θ/sec^2θ-1)+(cosec^3θ/cosec^2θ-1)=secθcosecθ(secθ+cosecθ)

Grade:10

1 Answers

Sakshi
23 Points
6 years ago
Sec^3theta/tan^2theta +cosec^3theta/cot^2theta because sec^2theta-1=tan^2theta after this put sectheta =1/costheta and tantheta=sintheta/costheta. And cosectheta=1/sintheta and. costheta=costheta/sintheta

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free